ANALISIS TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN NIKAH PADA SEKTOR PERDAGANGAN DI KOTA PEKANBARU - Ully Martha; Maulida Yusni; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the level of labor force participation, especially married women in the trade sector in Pekanbaru City. In this study, obtained from questionnaires and several direct interviews with related parties (respondents) and matters related to this research variable, namely the respondent's education level, husband's income and number of family members. By using multiple linear regression to test the hypothesis. The results showed that the R square value is 0.70, which means that 70% of the labor force participation of married women in the trade sector is influenced by the respondent's education level, husband's income and number of family members, while 30% is influenced by other variables. Simultaneous regression (mutually) of the independent variable has an influence on the dependent variable. Partially the variables of respondent education, husband's income and number of family members have a positive and significant effect on the level of labor force participation of married women in the trade sector in Pekanbaru City.Keywords: Married women labor force participation, trade sector, respondent education, husband's income, number of family members.